(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
At the beginning of the Eighties the Civic Museum of Rovereto Foundation started digitalizing and creating a website of the patrimony of data conserved and produced in the various sections. Over time a complex, but well structured architecture has been built, which enables precise research to be carried out using also thematic areas and geographical information. The principle continues to be one of collecting, conserving and sharing information, allowing researchers in different organizations also to collaborate in a common project, through use of the same platform. The photographic archives are a privileged sector for study and development that despite belonging not only to different archives but also to widely varied territories and subject matter, are nonetheless an exceptional means for carrying out what is one of the fundamental aims of a museum, that is telling the history of nature and humanity.